PATTERN OF OCULAR DISEASES IN PATIENTS ATTENDING A TERTIARY EYE CARE CENTER IN SOUTHERN ODISHA. - Radhakanta Bhoi; Dr Sabita Devi (Student's Journal of Health Research, 2023)
Objective: This retrospective study aimed to know the pattern of eye diseases in southern Odisha. Methods: A retrospective review of 2348 patients who had attended the OPD of the ophthalmology department, MKCG Medical College Berhampur over 1.5 months. The needed information was taken from patients' medical records. Results: Out of 2348 patients, 1364 (58.1%) were male and 984 (41.9%) were females with male to female ratio of 1.38:1.Refractive error (39.26%) was found to be the commonest ocular morbidity followed by conjunctival disorders (15.33%), cataract (14.6%), corneal disorders (10.52%), posterior segment disorders (5%), miscellaneous (4.77%), lid disorders (4%), trauma (3%), glaucoma (1.75%), and squint (1.15%). The study shows an exceeding number of male patients than females which implies that females are less aware of their health problems and ignorance and education an important causative factors. Conclusion: The leading causes of ocular morbidity in this study were refractive error, conjunctival disorder, cataracts, and corneal disorders. Recommendation: Preplacement vision screening and periodic vision screening are recommended for jobs that require visual acuity. Vision screening is recommended for post-injury and postoperative examinations.